Obligations in colombian law: evolutionary analysis since roman law - Cabrera, Lizandro (DIXI, 2024)
The importance of obligations in Colombian law and their evolution from Roman law is established. This research work delves into the origins, development, and, above all, the adaptation of such fundamental institutions as the law of obligations to national law. Colombian law, as a social science, is broad and generous in its protection of human beings, with roots that trace back to the beginnings of civilization. Legal science cannot forget its origins; by understanding them, it will be able to project itself toward the future of a new world based on reconciliation, tolerance, and coexistence. Colombia is a magnificent Social Rule of Law.